Amy Dunne, Spectacle, and Subversion : Interrogating the Male Gaze in Gone Girl (2014) through a Cross-Cultural Feminist Lens - Fahri Mulia Aria; Reza Dian Irawan Lubis; Zakaria Achmad; Rahmadsyah Rangkuti (Lembaga Pengembangan Kinerja Dosen, 2025)
This study presents a feminist analysis of the film Gone Girl (2014) through the theoretical lens of the male gaze concept proposed by Laura Mulvey. The study explores how the film deconstructs traditional patriarchal cinematic structures by repositioning the female protagonist, Amy Dunne, from an object of visual pleasure to an active subject who controls the narrative and psychological manipulation. Using qualitative content analysis methods, the study identifies key scenes and visual strategies that challenge the conventions of female representation in mainstream Hollywood cinema. The findings suggest that Gone Girl does not simply symbolically reverse gender roles, but also critically questions the mechanisms of spectatorism, representation, and power embedded in cinematic language. This study contributes to the broader discourse on gender and visual culture, by showing how contemporary cinema can be a space of resistance to normative feminine representations and patriarchal ideologies embedded in film production.